2017
DOI: 10.1016/j.cub.2017.08.065
|View full text |Cite
|
Sign up to set email alerts
|

Area Prostriata in the Human Brain

Abstract: Area prostriata is a cortical area at the fundus of the calcarine sulcus, described anatomically in humans [1-5] and other primates [6-9]. It is lightly myelinated and lacks the clearly defined six-layer structure evident throughout the cerebral cortex, with a thinner layer 4 and thicker layer 2 [10], characteristic of limbic cortex [11]. In the marmoset and rhesus monkey, area prostriata has cortical connections with MT+ [12], the cingulate motor cortex [8], the auditory cortex [13], the orbitofrontal cortex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
55
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 32 publications
(49 reference statements)
14
55
5
Order By: Relevance
“…Finally, we observed evidence of motion-related responses also in the ventral part of the calcarine scissure, where Mikellidou et al (2017) have recently identified the human prostriate area, a retinotopic region located medially in between RSC and PPA regions responsive to extremely fast motion over a wide visual field (see Supporting Information for details on the mapping procedures and Figure S2A for the anatomical position, MNI coordinates, and size of the region). The prostriate, although not activated on average by motion conditions relative to the Static condition as the PPA, revealed a preference for the Disjoint condition relative to Onboard (see Figure S2B).…”
Section: Cortical Areas Preferring Disjoint Movies (Inducing Objectmentioning
confidence: 61%
“…Finally, we observed evidence of motion-related responses also in the ventral part of the calcarine scissure, where Mikellidou et al (2017) have recently identified the human prostriate area, a retinotopic region located medially in between RSC and PPA regions responsive to extremely fast motion over a wide visual field (see Supporting Information for details on the mapping procedures and Figure S2A for the anatomical position, MNI coordinates, and size of the region). The prostriate, although not activated on average by motion conditions relative to the Static condition as the PPA, revealed a preference for the Disjoint condition relative to Onboard (see Figure S2B).…”
Section: Cortical Areas Preferring Disjoint Movies (Inducing Objectmentioning
confidence: 61%
“…Nonetheless, the small size and relative anonymity of this area has left it untouched by human neuroscientists peering inside the brain with tools such as fMRI. A new study by Mikellidou and colleagues in Current Biology [5] is thus bound to garner a lot of attention by providing the first functional description of area Prostriata in the human brain. The authors used a novel method to carry out fMRI mapping of responses to stimuli presented over an unusually wide range of positions, including the far periphery of the visual field.…”
mentioning
confidence: 99%
“…This can be particularly important when faced with sudden changes in environmental conditions, as in the case of looming stimuli, and is pivotal to self-motion stabilization, head and body orientation [6]. In keeping with this notion, the study by Mikellidou et al [5] provides the first example of functional preference for very fast motion in any human visual area. The physiological, connectional and anatomical properties of Prostriata together suggest an anatomical network for the analysis of motion in the far periphery that is largely segregated from that in well-studied cortical areas primarily devoted to central vision.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…described for the first time the functional properties of area prostriata in humans using a novel wide-field visual stimulation system (Greco et al 2016). In humans, area prostriata is located at the junction between the calcarine and parietooccipital (POS) sulci, adjacent to the far peripheral representation of V1 and ventral V2 (Mikellidou et al 2017b). Area prostriata preferentially responds to very fast motion, greater than 500 deg/sec, and has a complete representation of the visual field, clearly distinct from the adjacent area V1.…”
mentioning
confidence: 99%